Implementasi Program Home Visit dalam Meningkatkan Kesadaran Pendidikan Masyarakat Pesisir Panjang (Studi Kasus di SMA Negeri 2 Pekalongan) - Fatrisia, Ihda; Pramono, Didi (Ideas Publishing, 2024)
This study aims to determine the implementation, constaints, and impact of the Home Visit Program as an effort to increase educational awareness in the Panjang coastal community in overcoming the problem of dropout rates at SMA Negeri 2 Pekalongan. The approach in this research is qualitative research with data collection techniques, namely structured interviews, participant observation, and documentation. The results of this study are that the implementation of the Home Visit Program is going well because the responsible structures carry out their roles according to their status, but there are obstacles in its implementation, but it has an impact in reducing the dropout rate at SMA Negeri 2 Pekalongan, increasing the tri center of education and increasing awareness of the importance of education in the Panjang coastal community